KEANEKARAGAMAN JENIS BURUNG DI TELUK TAHUNA KABUPATEN KEPULAUAN SANGIHE - Jekson Wangka; Johny S. Tasirin; Martina A. Langi (COCOS, 2019)
ABSTRACT Tahuna is located on Sangihe Island which has a wealth of unique species of birds. Along the coast of Tahuna Bay there are three types of land cover namely the built area, coastal forest and mangrove forest, the difference in the existence of this area is followed by variations in the diversity of bird species, because found different types of birds from each type of habitat that made the observation point. The study was conducted at six locations using the point count method. This study aims to compare the diversity of bird species and communities in the built area, coastal forests and mangrove forests in Tahuna Bay. Data obtained from observations in the field will be analyzed with simple descriptive statistics and then displayed in tables and figures. Data analysis was performed to obtain species richness, diversity indexes, community similarities, and abundance and population. Data analysis was performed to evaluate species richness and density, biodiversity index, and community similarity. The results showed that in Tahuna Bay there were 27 species of birds from 15 families with the highest species richness in the Mangrove area which was low in human activity (15 species, 10 families) and the lowest wealth in the built area that was utilized for shops (5 species, 5 families) . The bird with the highest density in the Bay of Tahuan area is the Erasia Church Bird (Passer montanus) (K = 7.67 D / ha). Teluk Tahuna has a moderate species diversity index (H '= 2.28) with an evenness index from each observation point (E = 0.69). Natural areas (coastal forests and mangroves) have the highest community similarity value of (IS = 73%). Compared to the built area, which has the lowest community similarity value of (IS = 25%). Keywords: Bird Species Diversity, Tahuna Bay